Deaf adults and health care: Giving voice to their stories. Issue 9 (21st November 2013) - Sheppard, Kate
Abstract Purpose Deaf adults often experience significant healthcare disparities. This article gives voice to nine Deaf adults as they describe their lifelong experiences with health care. Data sources Qualitative, hermeneutic interviews with nine culturally Deaf adults. Each participant was interviewed three times, aided by a certified American Sign Language interpreter. Conclusions Participants recalled childhood memories of painful and frightening procedures to investigate the deafness, which frequently overshadowed emotional needs. Communication barriers between Deaf patients and providers left the patients not understanding the diagnosis or treatment, medication use, or side effects. Descriptions included distressing or embarrassing interactions, and cries for help gone unanswered. Consequently, minimal health promotion occurs and most participants rely on the emergency department for health care. Implications for practice Deaf patients should be screened for physical, sexual, and emotional abuse at every healthcare encounter. Assessments should include social support and social resources. Specific questions about pain, sleep, appetite changes, suicidal thoughts, and interest may help to identify manifestations of illness and health. Certified interpreters may be useful during the healthcare encounter, but ultimately the Deaf patient is best positioned to identify the most comfortable or meaningful means of communication between patient and healthcare provider.